ABCB1 gene variants and antidepressant treatment outcome: A meta‐analysis. Issue 4 (2nd April 2015) - Breitenstein, Barbara; Brückl, Tanja Maria; Ising, Marcus; Müller‐Myhsok, Bertram; Holsboer, Florian; Czamara, Darina
Abstract : The efflux pump P‐glycoprotein (P‐gp), a gene product of the ABCB1 gene, plays a pivotal role in the transfer of various molecules across the blood–brain barrier. P‐gp protects the brain by selectively extruding its substrates, including certain antidepressive drugs, thereby limiting their uptake into the brain. Uhr et al. [2008] first showed that ABCB1 variants predicted the remission to antidepressants with P‐gp substrate properties in patients suffering from major depression (MD). Other studies investigating the influence of ABCB1 polymorphisms on antidepressant treatment response produced inconclusive results. In this meta‐analysis, we systematically summarized 16 pharmacogenetic studies focused on the association of ABCB1 variants and antidepressant treatment outcome in patients with MD (overall n = 2695). We investigated the association of treatment outcome and six ABCB1 single nucleotide polymorphisms (SNPs): rs2032583, rs2235015, rs2235040, rs1045642, rs2032582, rs1128503. We stratified for admission status, ethnicity, and prescription of concomitant medication. SNP rs2032583 showed a nominally significant association across all studies ( P = 0.035, SNP was studied in a total of 2, 037 patients) and a significant Bonferroni‐corrected association among inpatients ( P = 1.5 × 10 −05, n = 485). Also SNP rs2235015 was significantly associated with antidepressant treatment outcome withstanding Bonferroni correction ( P = 3.0 × 10 −04 ) among inpatients in a smaller subsample (n = 195). There were no significant associations of the other SNPs tested with antidepressant treatment outcome. Future pharmacogenetic association studies should focus on the role of the ABCB1 SNP rs2032583 in antidepressant outcome prediction. © 2015 Wiley Periodicals, Inc.